A compreensão leitora de fábulas na perspectiva do ISD - Bezerra, Renata Uchoa (2020)
This research has as its object of study the teaching of reading the literary text in the elementary school classroom. With regard to reading, our study addresses the reading models, as well as the reading objectives proposed by Solé (1998). For data analysis, we are anchored in the studies developed by Bronckart (1999). The purpose of our research is to explore the language skills of 7th grade students enrolled in Portuguese language leveling classes. These students are from a full-time school in the city of Fortaleza and are in leveling classes because they have low performance in Portuguese. To explore the language skills of these students, the ISD theoretical framework conceives the organization of the text as a sheet consisting of three overlapping layers: the general infrastructure of the text, the textualization mechanisms and the enunciative mechanisms. Through a sequence of pedagogical activities we work with texts of the literary genre fable, a genre with predominance of the narrative sequence, which aims to train critical readers through the discussions that their stories provoke. The sequence of activities consists of an Initial Reading, five mediated steps and a Final Reading. From the results of the Initial Reading, the activities had a greater focus on verbal cohesion, since it was one of the items in which students had greater difficulty in mobilizing at the time of comprehension. The activities bring as a proposal, an interactive class contemplated in the sociopsycholinguistic model of Braggio (1992) and defended by Leurquin (2015). With regard to methodological aspects, the present research is characterized as an action-research, which according to Thiollent (2004), its main aspects considered are: wide and explicit interaction between researchers and people involved in the investigated situation. The results proved that teaching through a sequence of activities supported by the textual analysis categories of the ISD theoretical framework through the reading of literary texts of the genre fable, proved to be effective in the development of the language skills of the learners.